Tesla’s Global Impact: Reforming Indonesia’s Investment Policy for the Electric Vehicle Sector - Haliza Layla Tsabita; Zyunika Rahma; Armany Romadhon (LIBERATICA, 2025)
The global transition toward sustainable transportation has redefined the automotive industry, with electric vehicles (EVs) emerging as a key solution to reducing carbon emissions. In the United States, where transportation accounts for the largest share of greenhouse gas emissions, policies like the 7,500 EV tax credit and investments in charging infrastructure aim to achieve a 50% EV sales target by 2030. Tesla has become a leader in this transition, exemplifying how innovation can align environmental goals with financial success. Tesla’s global impact extends to emerging markets like Indonesia, which holds 21% of the world’s nickel reserves—critical for EV batteries. The Indonesian government has enacted legal frameworks, including the Omnibus Law and nickel export bans, to attract foreign investment and foster a domestic EV industry. However, the extent to which Tesla’s success has influenced these reforms remains underexplored. This study adopts a normative juridical approach, analyzing Indonesia’s investment laws and regulations through primary legal sources and secondary data. Findings suggest that Indonesia’s regulatory advancements, coupled with its resource strategy, position the nation as a competitive player in the global EV supply chain. This alignment between sustainability and economic growth highlights Indonesia’s potential as a hub for green industrial development.